2016
DOI: 10.1021/acs.orglett.6b00278
|View full text |Cite
|
Sign up to set email alerts
|

1,3-Dipolar Cycloadditions of Diazo Compounds in the Presence of Azides

Abstract: The diazo group has untapped utility in chemical biology. The tolerance of stabilized diazo groups to cellular metabolism is comparable to that of azido groups. Yet, chemoselectivity has been elusive, as both groups undergo 1,3-dipolar cycloadditions with strained alkynes. Removing strain and tuning dipolarophile electronics yields diazo group-selective 1,3-dipolar cycloadditions that can be performed in the presence of an azido group. For example, diazoacetamide but not its azido congener react with dehydroal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
81
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 66 publications
(82 citation statements)
references
References 56 publications
1
81
0
Order By: Relevance
“…Previously, we reported that the reaction of 1 and 8 proceeds with a rate constant of k = 1.6 × 10 −3 M −1 s −1 (Figure 1), which is 10 2 -fold less than that of trifluorocrotonate 2 . 10 Here, we found the rate constant for cycloaddition with crotonate 9 to be k = 5.8 × 10 −7 M −1 s −1 , which is 10 5 -fold less than that for trifluorocrotonate 2 . Notably, the effect of allylic fluorination in this reaction is much larger than is the effect of propargylic fluorination on the cycloaddition of azides (∼400-fold).…”
Section: Resultsmentioning
confidence: 63%
See 2 more Smart Citations
“…Previously, we reported that the reaction of 1 and 8 proceeds with a rate constant of k = 1.6 × 10 −3 M −1 s −1 (Figure 1), which is 10 2 -fold less than that of trifluorocrotonate 2 . 10 Here, we found the rate constant for cycloaddition with crotonate 9 to be k = 5.8 × 10 −7 M −1 s −1 , which is 10 5 -fold less than that for trifluorocrotonate 2 . Notably, the effect of allylic fluorination in this reaction is much larger than is the effect of propargylic fluorination on the cycloaddition of azides (∼400-fold).…”
Section: Resultsmentioning
confidence: 63%
“…22 Relative to the unfluorinated crotonate 9 , trifluorocrotonate 2 displays decreased distortion energies for both reacting partners, in addition to significantly larger interaction energies. The increased reactivity over acrylate 8 , however, stems not from a decreased distortion energy, as observed for typical cycloadditions of diazoacetamides, 10 but from a large increase in interaction energy (Δ E int ) that results from an N–H···F–C hydrogen bond formed between the diazoacetamide and a fluoro group of the trifluorocrotonate, along with hyperconjugative assistance to bond formation. Both hydrogen-bond formation 12d,23 and hyperconjugative assistance to bond formation have been asserted previously for cycloadditions with azides.…”
Section: Resultsmentioning
confidence: 88%
See 1 more Smart Citation
“…16 Accordingly, we observed an increase in reactivity for diazo groups with dipolarophiles containing electron-withdrawing substituents ( d and e ). 5,15b In contrast, azides show ambiphilic character—benefitting from both donors and acceptors on the dipolarophile. Still, electron-donating substituents on an alkene ( e.g.…”
Section: Resultsmentioning
confidence: 99%
“…21,22 Similarly, the diazo group is particularly attractive as a photoprobe and has enabled novel modications of proteins and nucleic acids 23 (New) because of its small size and ease of introduction within a short time. 24,25 The rst example of PAL was achieved with a diazoacetate.…”
Section: Diazo Compoundsmentioning
confidence: 99%